Faktor Determinan dan Motivasi Peserta KB Melalui Program KB Keliling untuk Memilih Metode Kontrasepsi Jangka Panjang - Ovi Hendrika; Maryadi Maryadi; Bambang Suprihatin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine what factors influence the selection of MKJP (Long Term Contraception Method) through the mobile family planning program in Prabumulih City. This research method is a quantitative analysis using secondary data from the 2021 Family Data Collection (PK21). The results showed that the Nagelkerke R Square value was 0.117 and Cox & Snell R Square 0.010, indicating that the independent variable's ability to explain the dependent variable is 0.010 or 1 percent. Ninety-one percent of other factors outside the model define the dependent variable. In conclusion, the element that has a significant influence on the selection of long-term contraceptive methods is the factor of access to family planning services. Keywords: Determinant Factors, Mobile Family Planning, Motivation